Cinnabar-containing Chinese medicine Hua-Feng-Dan differs from mercury sulfide and mercury chloride in affecting gut microbiota in mice - Yong-Mei Liu; Bo Liu; Jie Liu; Shang-Fu Xu; Feng Zhang; Ming-Liang Cheng; Jing-Shan Shi (Elsevier, 2023)
Introduction: Cinnabar (96% HgS) is included in Chinese medicines, including Hua-Feng-Dan. We have shown the protective effects of Hua-Feng-Dan against LPS plus rotenone-induced neurotoxicity in rats and against LPS plus MPTP-induced neuroinflammation in mice by modulation of gut microbiota. However, the effects of HgS-containing Hua-Feng-Dan in comparison to HgS and HgCl2 are unknown. Methods: Mice were given orally with Hua-Feng-Dan at clinical doses (0.6 and 1.5 g/kg), approximate Hg as HgS or HgCl2 for 7 days. Intestinal histology and Hg accumulation were examined. Bacterial DNA from the colon contents was extracted and subjected to DNA sequencing and qPCR verification with 16S rRNA probes. Results: Hua-Feng-Dan and HgS did not affect animal body weight gain, intestinal histology, nor produce overt intestinal Hg accumulation (2-fold). In contrast, HgCl2 reduced body weight gain, produced spotted mild inflammation, and produced 20-fold Hg accumulation in the duodenum. Operational taxonomic unit (OTU) from DNA sequencing showed that at phyla levels, HgS increased Firmicutes and decreased Bacteroidetes, while HgCl2 produced opposite effects; at the family levels, Hua-Feng-Dan increased Streptococcaceae and Dehalobacteriaceae, HgS had similar effects; at the genus levels, Hua-Feng-Dan and HgS increased Streptococcaceae__garvieae and Paraprevotellaceae__Prevotella, while HgCl2 increased Dehalobacteriaceae__Dehalobacterium and Odoribacteraceae__Odoribacter. HgS also increased Verrucomicrobiaceae__Akkermansia and produced many other alterations. Discussion: Cinnabar-containing Hua-Feng-Dan had minimal effects on animal health, gut histology and Hg accumulation but produced modulations of gut microbiota. Effects of Hua-Feng-Dan on gut microbiota were different from HgS and HgCl2.